Comparison between phase-transfer and cloud-point methodologies for the micellar extraction of biogenic amines - Romero, Lílian Mónica (2010)
We compared the recently developed surfactant-based extraction with sodium bis-[2-ethylhexyl]-sulphosuccinate (AOT) in heptane (the phase-transfer method) and the well established methodology with poly(oxyethylene)-7,5-(p-tert-octylphenyl) ether (Triton X-114; the cloud-point technique) to extract and preconcentrate biogenic amines. Both procedures were optimized and applied to the extrac-tion of biogenic amines from a beer sample. In order to improve the degree and monitoring of the extraction otherwise achieved with underivatized amines, the ﬂuorescent reagent dansyl chloride was used. Since the different procedures described in the literature are not in agreement, we optimized the derivatization reaction. Accordingly a systematic investigation of the experimental variables, one by one, yielded the following optimum conditions: dansyl chloride, 5mg/mL; 27 ◦C; reaction time, 25min; pH, 10.35 at ionic strength, 0.7mol/L. Both surfactant-based extraction procedures are simple and sensitive, but the use of AOT instead of Triton X-114 offers certain advantages. Detection limits of between 0.03 and 0.8 pmol injected were obtained when AOT was used, whose range is similar to or better than the other published techniques; while the corresponding values for Triton X-114 were between 0.2 and 1.2 pmol injected. The phase-transfer extraction is faster than the cloud-pointmethod, and no heating is required. For both approaches, the recovery was very high for all the amines studied and the reproducibility quite good for almost all. Upon comparison of calibration curves in pure water with those in the presence of samples, matrix effects were detected.